Wepose: Community Cares for Disadvantaged Children in Surabaya to Support The 4th SGD of Quality Education - Dita Nisaul Hidayah; Isa Anshori (Jurnal Indonesia Sosial Teknologi, 2025)
Quality education is an important element in sustainable development and improving the quality of a country's human resources. However, Indonesia is still lagging behind other countries in the global education system ranking. This study aims to analyze the role of the WEPOSE community in supporting the fourth point of sustainable development goals (SDGs) related to quality education in Surabaya. The research method used is qualitative descriptive with a phenomenological approach. Data was collected through interviews with WEPOSE Surabaya managers as well as literature studies from reliable sources. The research locations are at several points in Surabaya, including Wonokromo, Kalisari Damen, Pasar Turi, and Keputran. The results of the study show that WEPOSE Surabaya has existed since October 24, 2019, with the Founder of WEPOSE Surabaya Tabitha Naema Christy. This community is a community that cares about children's rights. Self-development activities that Surabaya youth participate in to support quality education are diverse, such as volunteering, community service, village teaching, community organizations, love of nature, youth mosques, ambassadors, beauty competitions, and many more. Not only that, the Surabaya City Government also coordinates with the East Java Provincial Government to ensure that Surabaya children get quality education. The conclusion of this study shows that the existence of communities like WEPOSE contributes significantly to the improvement of the education of underprivileged children. The implications of this study highlight the importance of collaboration between communities, governments, and other stakeholders in ensuring inclusive and sustainable quality education